PEMANFAATAN SARANG SEMUT (Myrmecodia pendens) ASAL KALIMANTAN SELATAN SEBAGAI ANTIBAKTERI - Crisnaningtyas, Farida (Kementerian Perindustrian, 2010)
The use of ant nests (Myrmecodia pendens) native of Borneo as an antibacterial. The aim of this research is to make the crude drug Â from the ant nest, simply extracting, condensing and test the ability of anti-bacterial properties of ant nests. This study covers the development of these extracts, proximate analysis, and test the antibacterial activity of plant-ant nest. Parameters measured were the growth of antibacterial activity against Salmonella sp., E. coli and Bacillus sp. showed by inhibition (clear zone). The results showed that plant-ant nests have antibacterial power. Ethanol extract of the ant nests provide a better inhibition compared with water extraction ant nests. Antibacterial activity of the ant nest extracts can be applied both in gram- positive and gram-negative bacteria. Key wood : ant nest, antibacterial,Â inhibition capability